2020
DOI: 10.5430/ijhe.v10n1p24
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Factors Affecting the Use of English Prepositions by Vietnamese Learners of English

Abstract: English prepositions play a significant role in helping students form a well-structured sentence in their learning and communicating. To help Vietnamese learners of English acquire their competence, the authors have done survey research to investigate the factors affecting the uses of English prepositions made by Vietnamese learners of English. The population included 200 female and 200 male participants. A total of 400 answers on the questions provided in the 100-question questionnaire were used for hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…English prepositional usage by Vietnamese learners is a context where this becomes particularly important, as errors in the learners' English prepositional usage may arise due to L1 conceptual transfer. The acquisition of English prepositions can be impacted by L1 conceptual transfer, leading to errors such as overgeneralization and underuse (Nghi et al, 2021). Prepositional usage in L2 learning has also been shown to be influenced by the L1 conceptual system in several other studies (Kim et al, 2020;Sumonsriworakun & Pongpairoj, 2017;Yildiz, 2016).…”
Section: B the Influence Of L1 Conceptual Transfer On Prepositional U...mentioning
confidence: 99%
See 1 more Smart Citation
“…English prepositional usage by Vietnamese learners is a context where this becomes particularly important, as errors in the learners' English prepositional usage may arise due to L1 conceptual transfer. The acquisition of English prepositions can be impacted by L1 conceptual transfer, leading to errors such as overgeneralization and underuse (Nghi et al, 2021). Prepositional usage in L2 learning has also been shown to be influenced by the L1 conceptual system in several other studies (Kim et al, 2020;Sumonsriworakun & Pongpairoj, 2017;Yildiz, 2016).…”
Section: B the Influence Of L1 Conceptual Transfer On Prepositional U...mentioning
confidence: 99%
“…According to findings by Hằng (2021) and Hung (2017), factors such as gender and L1 conceptual transfer can influence the acquisition of English prepositions amongst Vietnamese learners. When teaching and evaluating the way non-native English speakers use prepositions, language teachers and researchers need to consider these factors (Nghi et al, 2021).…”
Section: Studies On Vietnamese Learners Of English and Prepositional ...mentioning
confidence: 99%
“…Some other scholars the problems of the prepositions with respect to the cross linguistic influences (Demiral and Kaya 2 , 2016;Lowie and Verspoor, 2004;Nghi et. al., 2021) Likewise, Celce-Murcia and Larsen-Freeman (1983) state that English as second/foreign language teachers-as-a-group have feeling for that the English prepositions, following the linguistic unit 'articles', come as the second most difficult part of grammar for the students they teach.…”
Section: The Literature Review Of English Prepositionsmentioning
confidence: 99%
“…Studies regarding the complexity of learning and acquiring English prepositions by non-native speakers of English are varied and become a controversial issue. Nghi, et al (2021) investigated the factors that may influence the use of English prepositions by native speakers of Vietnamese. Their study, suggested that Vietnamese intra-lingual transfer negatively contributes to the prepositional sense stated by Vietnamese EFL learners.…”
Section: Previous Studymentioning
confidence: 99%